A monument to Lazarus: the leprosy hospital of Rio de Janeiro - Thomas Hunter Smith III (História, Ciências, Saúde: Manguinhos)
Soon after the Portuguese made landfall in 1500, Europeans and, later, African slaves introduced leprosy, and Saint Lazarus, the patron saint of its victims, into Brazil. Social and political pressure mounted by the middle of the eighteenth century in the city of Rio de Janeiro to remove those unfortunates from the city's streets even before the move of Brazil's capital in 1763. Frei Antônio, the bishop of Rio, founded the venerable hospital that year in the neighborhood of São Cristóvão. He requested that the Irmandade do Santíssimo Sacramento da Candelária provide oversight and administration. The brotherhood continues to honor its covenant of 239 years ago. The history of this hospital provides insight into the complex relationships that existed between the citizenry and church and state. Rio's leprosy hospital, now the Hospital Frei Antônio, had an important role in the evolution of the health care professions, progress in medical science, and the genesis of the hygienic movement in Brazil. This study also contributes to the history of a disease that persists in 2002 Brazil as a public health issue.